Mechanochemical synthesis, thermoanalytical study and characterization of new multicomponent solid forms of norfloxacin with saccharin - Ferreira, Patrícia Osório [UNESP]; de Moura, Aniele [UNESP]; de Almeida, Amanda Cosmo [UNESP]; dos Santos, Éverton Carvalho [UNESP]; Kogawa, Ana Carolina; Caires, Flávio Junior [UNESP] (Springer Nature, 2021)
Cocrystallization is a very efficient strategy to improve the physicochemical properties of bioactive agents. A new norfloxacin (NOR)–saccharin cocrystal and a cocrystal–solvate were synthesized through the mechanochemical method (neat and liquid-assisted grinding), and the characterization was performed by thermal analysis (TG–DTA, DSC and DSC microscopy), infrared vibrational spectroscopy and powder X-ray diffraction. Moreover, solubility experiments carried out in water and buffer solutions (pH 3.0, 6.1 and 8.5) showed that norfloxacin has an aqueous solubility 3.5 times higher when cocrystallized with saccharin than in its pristine state, and an inverted pH-dependency compared to NOR alone (2 times higher in 6.1, slightly increase in pH 3.0, and a decrease of 0.7 times in 8.5 buffer solution). Furthermore, the solvate–cocrystal has a water solubility 2.3 times higher than NOR and the same solubility in 6.1 buffer solution than the cocrystal (2 times higher than NOR alone).
Keywords: Mechanochemical synthesis; Norfloxacin; Pharmaceutical cocrystal; Saccharin; Solvate; Thermal analysis